Layanan Jakarta Pengawasan (Jakwas) Sebagai Inovasi Inspektorat Provinsi DKI Jakarta Untuk Pelaksanaan Pembinaan Dan Pengawasan Penyelenggaraan Pemerintahan Daerah Dalam Rangka Mewujudkan Clean Government - Alhaq, Reisya Tepi; Fienaurisilmi; Wan Fairuz Arkan Hibatullah; Delliq Hastariq Afthal; Ivan Darmawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The DKI Jakarta Inspectorate as a state apparatus is involved in achieving the goal of implementing clean government to emphasize the implementation of the principle of government integrity. The official portal of the DKI Jakarta Inspectorate has a JakWas service that needs to be studied as a catalyst and innovation in the implementation of guidance and supervision of the implementation of regional government. The study was conducted using a qualitative research method with a library/literature study data collection technique. The results of the study indicate that: 1) The DKI Jakarta Provincial Inspectorate in implementing guidance and supervision of the implementation of Regional Government innovates by creating a Jakarta Supervision (JakWas) dashboard to integrate SPBE services owned by the DKI Jakarta Inspectorate with the aim of increasing the effectiveness of supervision carried out by the DKI Jakarta Inspectorate on the implementation of Regional Government affairs by the DKI Jakarta Provincial Government Apparatus in an effort to realize clean government governance; 2) The creation of applications/information systems created by the DKI Jakarta Inspectorate is based on the mandate of regulations in accordance with the duties and functions of guidance and supervision; and 3) The implementation of sustainable programs requires a commitment to continue to carry out the task of guidance and supervision with excellence. Activities such as system evaluation, user feedback, effectiveness of SPBE services, and their impact on the implementation of provincial-level coaching and supervision duties.